Residential taxable value recovery in coastal Mississippi after Hurricane Katrina. Issue 3 (4th May 2019) - Krueger, Skip; Winkler, Julie; Schumann, Ronald L.
ABSTRACT: The resilience of local fiscal resources is an important missing component of community recovery after disasters. We know little about how quickly or fairly broad-based taxable economic activities return to pre-disaster levels. For example, property tax revenue, typically heavily dependent on residential properties, is commonly the largest source of General Fund revenue for local governments in the United States. Because residential properties are frequently impacted by natural hazards, understanding the linkage between housing and fiscal resilience is critical. Yet there exist very few broad-based studies of housing recovery. This paper helps fill that gap by evaluating housing recovery in a coastal portion of the U.S. state of Mississippi after Hurricane Katrina. We find that while the influence on housing values of Hurricane Katrina's flood and wind damage dwindled over time, race and income remained salient factors in the level of recovery of single-family homes and their taxable values.